Potential health effects of brewers' spent grain as a functional food ingredient assessed by markers of oxidative stress and inflammation following gastro-intestinal digestion and in a cell model of the small intestine. Issue 9 (21st April 2022) - Merten, Diane; Erman, Lara; Marabelli, Gianluca Pierluigi; Leners, Bernadette; Ney, Yannick; Nasim, Muhammad Jawad; Jacob, Claus; Tchoumtchoua, Job; Cajot, Sébastien; Bohn, Torsten
Abstract : Brewery spent grain increased dietary fiber when incorporated into bread, together with total phenolics and antioxidant capacity. This was retained after gastro-intestinal digestion. 150 g of such a bread can supply the recommended daily 25 g of fiber. Abstract : Brewer's spent grains (BSG) are a by-product of the beer-brewing industry, often employed as animal feeding stuffs. With BSG being rich not only in proteins, lipids, and dietary fiber but also in certain phytochemicals, it constitutes a potentially valuable food source that could be employed as a functional food, e.g. against chronic inflammatory diseases. Several types of bread were prepared with various amounts of BSG as flour replacement (0, 10, 20, 40, 60, 80 and 100%), either employing wet BSG or dried BSG after pressing. Total phenolics, flavonoids, insoluble dietary fiber, as well as antioxidant capacity (FRAP, ABTS) were measured in the bread, before and after simulated gastro-intestinal digestion. Furthermore, we investigated digested BSG and bread-containing BSG for their capability to alter oxidative stress (Nrf2, malondialdehyde) and inflammation (IL-6, IL-8, NO, and PGE2) in a Caco-2 cell culture model of the small intestine. Incorporation of BSG significantly and dose-dependently enhanced the amount of dietary fiber in the product, as well as total phenolics, flavonoids, and antioxidant capacity, by over 10-fold, 3-fold, 4-fold and 5-fold, respectively, when replacing all of the flour with BSG. This pattern remained after in vitro digestion. However, digesta failed to show significant antioxidant or anti-inflammatory effects on the biomarkers observed in the cell model. Consuming 150 g of such a BSG-bread (wet based) would supply the proposed RDA of 25 g d −1 dietary fiber and could be a healthy product valorizing BSG.